2015
DOI: 10.1016/j.apgeog.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of distance in peri-urban national park use: Who visits them and how far do they travel?

Abstract: a b s t r a c tThere is a sizable literature about the factors shaping park visitation and use e especially for urban parks, including (i) geographic (e.g. proximity), (ii) socio-cultural (e.g. population characteristics) and to a lesser extent, (iii) individual psychometric factors (e.g. attitudes and values). Yet comparatively little is known about how factors related to distance may affect peri-urban national park use, particularly outside the United States. This paper reports on research investigating dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 83 publications
(121 reference statements)
5
45
1
3
Order By: Relevance
“…In the case of this study into millennial motivations, this would then imply that younger people are in fact less likely to travel farther distances but older populations would. Another study tested distance-decay theory on Brisbane's D'Aguilar National Urban Park in Australia and findings revealed that peak visitation came from visitors five to ten kilometers away in order to specifically undertake experiences local neighborhood parks could not offer [8]. Significantly, this study also showed that millennials were in fact more likely to visit parks and green spaces located further distances from them than older populations [8].…”
Section: Distance Decaymentioning
confidence: 67%
See 4 more Smart Citations
“…In the case of this study into millennial motivations, this would then imply that younger people are in fact less likely to travel farther distances but older populations would. Another study tested distance-decay theory on Brisbane's D'Aguilar National Urban Park in Australia and findings revealed that peak visitation came from visitors five to ten kilometers away in order to specifically undertake experiences local neighborhood parks could not offer [8]. Significantly, this study also showed that millennials were in fact more likely to visit parks and green spaces located further distances from them than older populations [8].…”
Section: Distance Decaymentioning
confidence: 67%
“…For these reasons, the demographics are different from national park users and vary from one urban park to another according to the demographics of the local community within which the park is located. Although a general profile of Toronto urban park users cannot be defined, previous studies have shown that urban park users typically live within five kilometers and visits are short, yet frequent, mainly to conduct exercise routines [8]. In saying this, the leading motivations to visit urban parks will vary between location depending on the design and layout, but the desire to appreciate nature is always paramount.…”
Section: Urban Parks Urban National Parks and The Benefits Of Visitingmentioning
confidence: 99%
See 3 more Smart Citations